Assessment the awareness toward hypertension and diabetes mellitus: Syrian cross sectional study - Sarya Swed; Hidar Alibrahim; Haidara Bohsas; Wael Hafez; Stanisław Surma; Mohammed Amir Rais; Hesham Mohamed Abuelsaoud; Rehab Mohamed Elshazly; Sheikh Shoib; Bisher Sawaf; Amr Farwati; Mohammed Najdat Seijari; et al. (BMC, 2023)
Abstract Background Diabetes and arterial hypertension are the two most common types of non-communicable diseases (NCDs) impacting people globally. There is no prior research on the Syrian population's knowledge and treatment of hypertension and diabetes. It is crucial to investigate how the Syrian public understands and perceives these disorders in order to address the increased incidence and prevalence of hypertension and diabetes. This research intends to assess the level of hypertension and diabetes-related awareness, knowledge, attitude, and practices among Syrian individuals. Methods A cross-sectional survey was conducted online between 1 August and 25 August 2022. The questionnaire for the study was developed based on previous research, and the inclusion criteria for the sample were Syrian residents older than 18 who presently live in Syria. The survey consisted four sections: sociodemographics information, WHO STEPS survey instrument on knowledge of and lifestyle determinants for hypertension and diabetes, respondents' knowledge of and comprehension of hypertension and diabetes, and respondents' awareness of these disorders. Results Among 976 participants, 65.8% were females. the most common causes for hypertension from the perspective of participants were (90.1%) for stress, (87%) High salt consumption, (82.1%) genetics, (78.2%) old age, (78%) obesity (69%) anxiety, and (38.6%) for drug usage. Primary and middle school educational status participants had greater hypertension knowledge (92.3%) than other educational levels. There was a statistical significant difference between the knowledge toward the hypertension and the drinking alcohol, which the nonalcoholic knowledgeable persons were the most common (819 / 976)(P < 0.05). Participants whose lifestyles did not include alcohol use had a higher hypertension knowledge level (90.3%). Participants who do not consume alcohol have shown better hypertension knowledge (90.3%) than those who do (81.9%). Almost age groups have shown good knowledge of diabetes, especially participants aged above 55 (93.8%). However, most individuals have examined blood pressure (82.3%), whereas fewer than half had screened for blood sugar (64.4%). About 82.2% of individuals check their blood pressure frequently, whereas 6.2% monitor their blood sugar. There were significant associations between hypertension knowledge and gender, education, employment, and economic position (P value < 0.05). Men (mean = 8.39, SD = 2.02, P-value < 0.05) have a higher hypertension knowledge than females, and knowledge of hypertension among participants was shown to be higher among those in good income status than other economic levels (mean = 8.34, SD = 1.98). Age, gender, education, employment, and marital status were all associated with diabetes knowledge. Participants between the ages of 40 and 55 showed better knowledge of diabetes compared to other age groups (mean = 11.32, SD = 2.54); also, men demonstrated greater knowledge of diabetes than females (mean = 10.76, SD = 2.79). Conclusion We indicated that the Syrian population has a good to moderate understanding of hypertension and diabetes. However, there is still a shortage of standardized, regular screening practices. Since individuals remain involved in unhealthy lifestyle habits, it is vital to provide accurate information about hypertension and diabetes to encourage them to make healthy changes.